Spacers-directed structural diversity of Co(II)/Zn(II) complexes based on S-/O-bridged dipyridylamides: electrochemical, fluorescent recognition behavior and photocatalytic properties. Issue 4 (16th February 2018) - Liu, Guo-Cheng; Li, Yan; Xiong, Ying; Liu, Xiang-Xiang; Li, Qiao-Min; Zhang, Ju-Wen; Lin, Hong-Yan; Li, Xiao-Wu
Abstract: To investigate the effect of the spacers of S-/O-bridged dipyridylamides on the structures of Co(II)/Zn(II) complexes, [Co(L 1 )(chda)]·1.5H2 O (CP1 ), [Co(L 2 )(chda)] (CP2 ), [Zn(L 1 )(hip)]·DMA·2H2 O (CP3 ), and [Zn(L 2 )(hip)]·2.8H2 O (CP4 ) [L 1  =  N, N′ -bis(pyridine-3-yl)thiophene-2, 5-dicarboxamide, H2 chda =  trans -1, 4-cyclohexanedicarboxylic acid, L 2  =  N, N′ -bis(pyridine-3-yl)-4, 4′-oxybis(benzoic) dicarboxamide, H2 hi p  = 5-hydroxyisophthalic acid, DMA =  N, N -dimethylacetamide], have been solvothermally synthesized. X-ray single-crystal diffraction shows thatCP1 is a 2-D 3, 5-connected network based on Co-L 1 linear chains and (Co-chda)2 double chains.CP2 features a 1-D structure derived from 1-D wave-like (Co-chda)2 double chains decorated by terminal L 2 ligands.CP3 andCP4 show wave-like (4, 4) networks constructed by 1-D Zn-L 1 zigzag and Zn-hip zigzag (forCP3 )/linear (forCP4 ) chains. The effect of the spacers of S-/O-bridged dipyridylamides on the structures of the title complexes was discussed. Electrochemical behaviors ofCP1 –CP2 and solid-state luminescent properties ofCP3 –CP4 were studied. The luminescence investigations show thatCP3 andCP4 are recycled fluorescent probes for environmentally relevant Fe 3+ ions. The photocatalytic properties for the degradation of methylene blue (MB) under ultraviolet light irradiation ofCP3 –CP4 and the recyclable materials after fluorescent sensing Fe 3+ ions (namedCP3 @Fe 3+ andCP4 @Fe 3+ ) have also been investigated. Abstract :